2022
DOI: 10.3389/feduc.2022.978796
|View full text |Cite
|
Sign up to set email alerts
|

Pre-licensure medical students’ knowledge and views on interprofessional learning: A qualitative concept analysis based on real-world data

Abstract: BackgroundThe several definitions of Interprofessional Education (IPE) allow for different interpretations and interchangeable terms. This study aims to determine the characteristics and attributes of the definition of IPE.Materials and methodsIn November 2019, 31 medical students (64.5% female) from a single institution took part in nine semi-structured interviews. We created a deductive three-level code system followed by an inductive code system based on several known IPE definitions. We extracted the main … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…While the aforementioned literature focuses on supervisor–student interactions, nursing and medical students have also been found to value learning through interacting interprofessionally and with patients ( 28 , 29 ). Studies have demonstrated that interprofessional collaboration enables students to learn about each other’s professional roles, view patients’ situations from a holistic perspective, and communicate with each other effectively and respectfully ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the aforementioned literature focuses on supervisor–student interactions, nursing and medical students have also been found to value learning through interacting interprofessionally and with patients ( 28 , 29 ). Studies have demonstrated that interprofessional collaboration enables students to learn about each other’s professional roles, view patients’ situations from a holistic perspective, and communicate with each other effectively and respectfully ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%